The Joint Effect of Management's Prior Forecast Accuracy and the Form of Its Financial Forecasts on Investor Judgment - Hirst, D. Eric; Koonce, Lisa; Miller, Jeffrey (Journal of Accounting Research, 1999)
D. Eric Hirst, Lisa Koonce, Jeffrey Miller, The Joint Effect of Management's Prior Forecast Accuracy and the Form of Its Financial Forecasts on Investor Judgment, Journal of Accounting Research, Vol. 37, Studies on Credible Financial Reporting (1999), pp. 101-124